Rebound! : The Incredible Story of UConn Basketball's Comeback from Defeat to Dominance - Borges, David (Book collections on Project MUSE., 2015)
In September 2012, legendary University of Connecticut men's basketball coach Jim Calhoun-who had won three national championships, the last in 2011-abruptly retired. His handpicked replacement was Kevin Ollie, a former UConn player and longtime NBA journeyman who had returned two years earlier to be Calhoun's assistant. Ollie was widely praised as a "basketball savant" and respected by virtually everyone who knew him. But he had no head coaching experience-at any level-before taking the UConn job. He was also inheriting a mess. Due to past academic problems, UConn was barred from postseason page.